Tradisi Bhe’ Gerbis; Perpaduan Agama Dan Seni Lokal Madura (Studi Kasus di Desa Rajun Pasongsongan Sumenep) - Hayatulah (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
This research tries to reveal the Bhe' Gherbis tradition in Rajun Pasongsongan as a local art and cultur mixed with religious views and values. This research is a field research with a qualitative approach. The data analysis used is interactive analysis of Miles and Huberman model having three stages and activities simultaneously: data reduction, data disply and conclusion drawing/verification. The results of research show that: a) traditions that have become habits in society have taken root and become religious rituals by some people. This cannot be separated from the indigenous Islamic mission and thoughts which promote the preservation of religion, but do not eliminate the traditions inherited from their ancestors; b) traditions are built from the local community's philosophy of life which is processed based on views and life values ​​whose truth and benefits are recognized. c) the entry of Islam into the archipelago and in subsequent developments there have been cultural interactions that influence each other. d) Local art which combined with Islamic phrases, becomes a new attraction for the Rajun community without causing significant tension